2012
DOI: 10.1080/09243453.2012.728135
|View full text |Cite
|
Sign up to set email alerts
|

The achievement effects of tardy classmates: evidence in urban elementary schools

Abstract: In evaluating the deleterious effects of missing in-school time, research has almost exclusively focused on absences, and almost no attention has been paid to tardiness. Hence, this study contributes a new dimension to the field by examining the effects of student tardiness on academic achievement. Employing an empirical model on a large-scale, longitudinal, multilevel dataset of urban elementary school children over 6 years of observations, there are 2 significant findings. First, students with greater tardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…Above and beyond academic achievement, behavioral measures such as self‐management (Robbins, Allen, Casillas, Peterson, & Le, ) and temperament (Camara, ) positively influence performance, not only in K‐12 and college settings, but also in the workplace (ACT, ). Attendance and disciplinary actions may be the most popular ways to operationalize concepts like self‐management and temperament in middle school (Allensworth & Easton, ; Balfanz, Herzog, & Mac Iver, ), but additional variables such as tardiness (Gottfried, ), suspensions (Arcia, ), and study habits (Cooper, Robinson, & Patall, ) are also associated with future academic success.…”
Section: Background and Conceptual Frameworkmentioning
confidence: 99%
“…Above and beyond academic achievement, behavioral measures such as self‐management (Robbins, Allen, Casillas, Peterson, & Le, ) and temperament (Camara, ) positively influence performance, not only in K‐12 and college settings, but also in the workplace (ACT, ). Attendance and disciplinary actions may be the most popular ways to operationalize concepts like self‐management and temperament in middle school (Allensworth & Easton, ; Balfanz, Herzog, & Mac Iver, ), but additional variables such as tardiness (Gottfried, ), suspensions (Arcia, ), and study habits (Cooper, Robinson, & Patall, ) are also associated with future academic success.…”
Section: Background and Conceptual Frameworkmentioning
confidence: 99%
“…Student academic performance and school engagement is associated with environments that lack stability in terms of student mobility (e.g., Gruman et al, 2008; Mehana & Reynolds, 2004; Parke & Kanyongo, 2012). Furthermore, truancy, absenteeism, and school suspension, are all associated with poorer developmental outcomes including lower high school graduation rates, higher rates of reported depression and other mental disorders, and increased delinquency (Gottfried, 2014; Havik et al, 2015; Johnson et al, 2015; Kearney & Ross, 2014). In contrast, nurturing relationships such as teacher support and availability of mentoring relationships have been associated with school success (Estell & Perdue, 2013; Garcia-Reid, Peterson & Reid, 2015; Hurd & Sellers, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on tardiness at school are limited, although it has been a research topic since 1930, e.g., Lockwood [30]. More recent studies, carried out nearly 75 years later by Gottfried [31] in the US, show that tardiness is a risk for school achievement in math and reading not only for individual students but also for their classroom peers. In addition, students who arrive late to the classroom pose a risk for others being tardy (ibid.).…”
Section: Specific On Tardinessmentioning
confidence: 99%
“…In addition, students who arrive late to the classroom pose a risk for others being tardy (ibid.). In a study of 250 junior high school students, Gottfried [31] found that on average, boys were tardy more frequently than girls, but that half the students in the school had no incidence of tardiness.…”
Section: Specific On Tardinessmentioning
confidence: 99%